STRUKTUR DAN FUNGSI BAMANG BABOIS DAN BAMANG BATIBAS MASYARAKAT DAYAK SALAKO DI DESA PAJINTAN - Elofhia, Loriya; Effendy, Chairil; Nadeak, Parlindungan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the lack of conservation effort toward oral literature of Salako Dayaknese. General issues are the structure and function of the bamang Babois and bamang Batibas. The purpose of this research is to describe and analyze the issues discussed. This research uses descriptive method with qualitative research form and structural approach. Sources of data in this research are bamang Babois and bamang Batibas text. Data in this research are in the quote that belong to the category of diction, imagery, concrete words, sounds, and function. The results of the analysis showed that bamang Babois and bamang Batibas structure consisted of almost identical dictions, imageries, concrete words, rhythms and rhymes. The function of both bamang Babois and bamang Batibas are as a projection system, as a tool of cultural validation, as a tool of children's education, and as a tool of coercion and controller of social norms. Keywords:  Structure, Function, Bamang Babois, Bamang Batibas